Breaking Away from the 'POISONOUS' Habit - Abd Razak, Dzulkifli (1995)
GIVEN THE INSIDIOUS AND PERVASIVE nature of poisoning associated with cigarette smoking, the surest way to prevent such poisoning is to QUIT. However to break any bad habit is never a simple matter. According to a Gallup Poll, that success rate is rather dismal. This is mainly due to the addictive properties of nicotine. You need an enormous amount of willpower to sustain such an effort to kick the habit of smoking. The whole process perhaps is a that of relearning, that is, to once again learn how to live without cigarettes. After all, cigarette smoking, like other drugs of abuse, is indeed a learned behaviour and much of this has to be unlearned before one can successfully call it a quits. As such, there are no hard and fast rules about how to stop smoking. It therefore important to recognise some of the barriers associated with the process of quiting.